Linked color imaging (LCI), a novel image-enhanced endoscopy technology, emphasizes the color of early gastric cancer - Kanzaki, Hiromitsu; Takenaka, Ryuta; Kawahara, Yoshiro; Kawai, Daisuke; Obayashi, Yuka; Baba, Yuki; Sakae, Hiroyuki; Gotoda, Tatsuhiro; Kono, Yoshiyasu; Miura, Ko; Iwamuro, Masaya; Kawano, Seiji; Tanaka, Takehiro; Okada, Hiroyuki (Endoscopy International Open, 2017)
Background and study aims Linked color imaging (LCI) and blue laser imaging (BLI) are novel image-enhanced endoscopy technologies with strong, unique color enhancement. We investigated the efficacy of LCI and BLI-bright compared to conventional white light imaging (WLI) by measuring the color difference between early gastric cancer lesions and the surrounding mucosa.Patients and methods Images of early gastric cancer scheduled for endoscopic submucosal dissection were captured by LCI, BLI-bright, and WLI under the same conditions. Color values of the lesion and surrounding mucosa were defined as the average of the color value in each region of interest. Color differences between the lesion and surrounding mucosa (ΔE) were examined in each mode. The color value was assessed using the CIE L*a*b* color space (CIE: Commission Internationale d’Eclairage).Results We collected images of 43 lesions from 42 patients. Average ΔE values with LCI, BLI-bright, and WLI were 11.02, 5.04, and 5.99, respectively. The ΔE was significantly higher with LCI than with WLI (P < 0.001). Limited to cases of small ΔE with WLI, the ΔE was approximately 3 times higher with LCI than with WLI (7.18 vs. 2.25). The ΔE with LCI was larger when the surrounding mucosa had severe intestinal metaplasia (P = 0.04). The average color value of a lesion and the surrounding mucosa differed. This value did not have a sufficient cut-off point between the lesion and surrounding mucosa to distinguish them, even with LCI.Conclusion LCI had a larger ΔE than WLI. It may allow easy recognition and early detection of gastric cancer, even for inexperienced endoscopists.